PENDIDIKAN EKONOMI MENURUT PERSPEKTIF AL-QURAN - Wahyudi Hidayah; Ahmad Zumaro (Widya Balina, 2025)
The purpose of this study is to identify the concept of economic empowerment for Muslims in the Qur'an and to understand its role in life. The threat of poverty and powerlessness can undermine faith, morals, security stability, and create social dissatisfaction. Therefore, through verses in the Qur'an, the researcher will discuss the economic empowerment of Muslims from a Qur'anic perspective. The research method used is the maudlu'i interpretation of economics, which includes the following steps: first, collecting verses relevant to the economic issues to be analyzed, both based on keywords and the content of the verses in general and specifically. Second, interpreting these verses by following the sequence of verses in the Mushaf or based on the chronology of the revelation of the surahs. Third, the interpretation model applied is maudlu'i by linking them to the real conditions of the economy. In this study, researchers will examine data contained in the Qur'an, tafsir, hadith, as well as books and journals related to the meaning of economic empowerment of Muslims. The concept of economic empowerment of Muslims from the perspective of the Qur'an is to free individuals from injustice, empower human potential, and encourage individuals to care for others, towards happiness in this world and the hereafter. The role of economic empowerment of Muslims in life includes: contributing to eliminating the practice of usury, human trafficking, monopoly of wealth, and power that triggers poverty, hunger, and fear. In addition, it also motivates individual Muslims to be strong, resilient, persistent, and strive earnestly and not give up.